2019
DOI: 10.1101/813675
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A model for the emergence of RNA from a prebiotically plausible mixture of ribonucleotides, arabinonucleotides and 2’-deoxynucleotides

Abstract: The abiotic synthesis of ribonucleotides is thought to have been an essential step towards the emergence of the RNA world. However, it is likely that the prebiotic synthesis of ribonucleotides was accompanied by the simultaneous synthesis of arabinonucleotides, 2′-deoxyribonucleotides, and other variations on the canonical nucleotides. In order to understand how relatively homogeneous RNA could have emerged from such complex mixtures, we have examined the properties of arabinonucleotides and 2′-deoxyribonucleo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 47 publications
1
12
0
Order By: Relevance
“…and heterogeneous oligonucleotides that could have coexisted alongside oligoribonucleotides could also promote strand displacement via the formation of invaders. Recent work in our lab (Kim et al, 2019) has shown that oligonucleotides ending in a 3′-arabino nucleotide cannot be further extended, providing a mechanism for the generation of short invaders that are inert to copying chemistry. Thus, the products of both degradative reactions and stalled replicative processes could contribute an essential function to genomic replication.…”
Section: Discussionmentioning
confidence: 99%
“…and heterogeneous oligonucleotides that could have coexisted alongside oligoribonucleotides could also promote strand displacement via the formation of invaders. Recent work in our lab (Kim et al, 2019) has shown that oligonucleotides ending in a 3′-arabino nucleotide cannot be further extended, providing a mechanism for the generation of short invaders that are inert to copying chemistry. Thus, the products of both degradative reactions and stalled replicative processes could contribute an essential function to genomic replication.…”
Section: Discussionmentioning
confidence: 99%
“…RNA has an exceptional double helical structure with the ribose sugars in the 3’- endo conformation; as a consequence the RNA primer/template/intermediate complex is preorganized so as to favour rapid primer extension. Our experiments show that in this context, RNA copying has a significant kinetic advantage over alternative nucleic acids including not only TNA, but also ANA and DNA(26). Our experimental results are therefore consistent with a model in which relatively homogeneous RNA oligonucleotides emerged from a much more heterogeneous mixture of activated nucleotides through the self-purifying capacity of nonenzymatic RNA replication.…”
Section: Discussionmentioning
confidence: 79%
“…We therefore attempted to observe the formation of the corresponding TNA dinucleotide intermediate under primer extension conditions (Figure 2C). When we incubated purified 2AIptC at a concentration of 60 mM at pH 8 and followed the reaction by 31P-NMR, we found that the imidazolium-bridged TNA dinucleotide is formed, but the observed rate of 8.8 * 10 -4 hr -1 mM -1 is approximately 4 to 5 fold slower than the corresponding rates for the activated ribonucleotides 2AI-rA and 2AI-rC (3.2 and 4.5 * 10 -3 hr -1 mM -1 )(26,27) (Figure 2D). This result suggests that the slow rate of primer extension with activated threo-nucleotide monomers is due at least in part to the slower formation of the necessary imidazolium-bridged intermediate.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Since protocells’ origin, natural pigments have transformed into various phenomena such as pigments, fluorescence, and bioluminescence, found in prokaryotes and eukaryotes. Currently, researchers believe that life had originated 4.5 billion years ago from the extreme environment like hydrothermal vents in the ocean [ 130 ] or warm water pools in the volcanic land or geothermal (hot spring) areas [ 129 , 131 , 132 ], based on the evidences of hypothetic protocell structures, i.e., vesicles formed by simple fatty acids [ 130 ] and proteins [ 133 ], RNA [ 131 ] and DNA molecules [ 129 ]. The abundant external red pigments seen in deep-sea tubeworms at hydrothermal vents are indeed hemoglobins that act as binding sites to oxygen and hydrogen sulfide and transport these molecules to internal bacterial symbionts [ 134 ].…”
Section: Evolution Of Pigmentsmentioning
confidence: 99%